Pengaruh PBB dan BPHTB terhadap Pendapatan Asli Daerah (PAD) dengan Metode Systematic Literature Review (SLR) - Tiar Lina Situngkir; Nafisah Dwi Yuliarida; Siti Nurazizah; Nadira Aisha Amidia; Nurmala Dewi Rahmawati; Muhammad Rama Rizaldi; Priambudi; Qobus Rayhaan Al Awaludin; Alvito Auliansyah; Tegar Dwi Fajriatama (Economic Reviews Journal, 2024)
When using the Systematic Literature Review (SLR) technique, the research objective is to examine the impact of PBB and BPHTB on PAD. This research identifies, assesses, and synthesizes previous relevant works bringing together many sources in Sprott-approved journals on this topic. The results of this research show that, although at different levels, PBB and BPHTB make significant contributions to PAD in various regions in Indonesia. Increasing revenue from the PBB and BPHTB sectors is one strategy to increase PAD. However, a number of regions still experience difficulties in maximizing revenue from these two tax categories, including low effectiveness and PAD contributions which are in the low to medium range. In addition, this research found that PBB has a significant and beneficial influence on regional economic growth, although the impact of  BPHTB on this cannot yet be determined. The overall results of this research highlight the important role of PBB and BPHTB in increasing PAD and regional economic growth, so it is important for local governments to maximize management and increase revenue from these two types of taxes.